EKSPERIMENTASI MODEL BLENDED LEARNING MASA PANDEMIK COVID-19 TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VII SMP NEGERI 23 KABUPATEN TEBO - Agus Jasmadi, S.Pd (Pendidikan Matematika | STKIP YM Bangko, 2022)
The purpose of this study was to describe mathematical communication skills using a blended learning model better than face-to-face limited learning. This study uses a quantitative approach with experimental methods. The population of this study were all students of class VIII SMP Negeri 23 Tebo, totaling three classes with a sample of class VIII A as the experimental class and class VIII B as the control class. The instrument used is a test of mathematical communication skills in the form of a description. The results of the data analysis requirements show that the data of the two sample classes are normally distributed and the variance is homogeneous. Hypothesis testing uses parametric statistical formulas for the two-mean difference test, namely independent sample t-test (two independent sample t-test). Based on the results of the analysis of research data, it shows that the tcount is greater than the ttable or 1.931 > 1.669 in the one-sided test. Because the value of tarithmetic is greater than the value of ttable , then Ho rejected and H1 is accepted, so it can be concluded that mathematical communication skills with the blended learning model are better than limited face-to-face learning for class VIII students of SMP Negeri 23 Tebo